1972
DOI: 10.1126/science.178.4065.1102
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic and Cholinergic Innervation of the Hamster Harderian Gland

Abstract: Examination of Harderian glands of adult male and female golden hamsters by appropriate histochemical techniques reveals that adrenergic nerves are associated only with the blood vessels. Acetylcholinesterase-positive fibers are present in the connective tissue surrounding the gland, along the ducts, and among the acini.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1973
1973
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In mammals, Huhtala et al (1977) also observed AchE-positive nerves along the blood vessels of the rat Harderian gland, while Norvell and Clabough (1972) did not find such in the hamster. The latter authors suggested that the modification of blood flow in the hamster gland is mainly due to adrenergic fibers.…”
Section: Innervationsmentioning
confidence: 79%
“…In mammals, Huhtala et al (1977) also observed AchE-positive nerves along the blood vessels of the rat Harderian gland, while Norvell and Clabough (1972) did not find such in the hamster. The latter authors suggested that the modification of blood flow in the hamster gland is mainly due to adrenergic fibers.…”
Section: Innervationsmentioning
confidence: 79%
“…4) (Brownscheidle and Niewenhuis, 1978;Bucana and Nadakavukaren, 1972;Huhtala et al, 1977;Norvell and Clabough, 1972;Sakai and Yohro, 1981;Watanabe, 1980). Additionally, nerve fibers in rat Harderian glands contain vasoactive intestinal polypeptide (VIP), cholecystokinin (CCK), neurotensin (NT), calcitonin gene-related peptide (CGRP), and neuropeptide Y (NPY) (Tsukahara and Jacobowitz, 1987).…”
Section: Secretory Mechanismmentioning
confidence: 99%
“…In the unilaterally blinded group, half of each gland was processed for hematoxylin and eosin, and half for fluorescent micro scopy. Because the adrenergic innervation was also beingexamined in the Harderian glands of some of these animals [Norvell and C labough, 1972] …”
Section: Methodsmentioning
confidence: 99%